A Randomized Controlled Clinical Trial in Healthy Older Adults to Determine Efficacy of Glycine and N-Acetylcysteine Supplementation on Glutathione Redox Status and Oxidative Damage - Lizzo, Giulia; Migliavacca, Eugenia; Lamers, Daniela; Frézal, Adrien; Corthesy, John; Vinyes-Parès, Gerard; Bosco, Nabil; Karagounis, Leonidas G.; Hövelmann, Ulrike; Heise, Tim; von Eynatten, Maximilian; Gut, Philipp (Frontiers in Aging, 2022)
Glycine and cysteine are non-essential amino acids that are required to generate glutathione, an intracellular tripeptide that neutralizes reactive oxygen species and prevents tissue damage. During aging glutathione demand is thought to increase, but whether additional dietary glycine and cysteine intake contributes towards the generation of glutathione in healthy older adults is not well understood. We investigated supplementation with glycine and n-acetylcysteine (GlyNAC) at three different daily doses for two weeks (low dose: 2.4g, medium dose: 4.8g or high dose: 7.2g/day, 1:1 ratio) in a randomized, controlled clinical trial in 114 healthy volunteers. Despite representing a cohort of healthy older adults (age mean = 65 years), we found significantly higher baseline levels of markers of oxidative stress, including that of malondialdehyde (MDA, 0.158 vs. 0.136, µmol/L, p<0.0001), total cysteine (Cysteine-T, 314.8 vs. 276, µM, p<0.0001), oxidized glutathione (GSSG, 174.5 vs. 132.3, µmol/L, p < 0.0001), and a lower ratio of reduced to oxidized glutathione (GSH-F:GSSG) (11.78 vs. 15.26, p=0.0018) compared to a young reference group (age mean=31.7 years, n=20). GlyNAC supplementation was safe and well tolerated by the subjects, but did not increase levels of GSH-F:GSSG (end of study, placebo=12.49 vs 7.2g=12.65, p-value=0.739) or that of total glutathione (GSH-T) (end of study, placebo=903.5 vs 7.2g=959.6, mg/L, p-value=0.278), the primary endpoint of the study. Post-hoc analyses revealed that a subset of subjects characterized by high oxidative stress (above the median for MDA) and low baseline GSH-T status (below the median), who received the medium and high doses of GlyNAC, presented increased glutathione generation (end of study, placebo=819.7 vs. 4.8g/7.2g=905.4, mg/L, p-value=0.016). In summary GlyNAC supplementation is safe, well tolerated, and may increase glutathione levels in older adults with high glutathione demand.